Effects of algae-derived β-glucans with zinc on nursery pig growth performance and immune response under commercial conditions - Marcio Antonio Dornelles Goncalves; Steven S Dritz; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jason C Woodworth (Kansas Agricultural Experiment Station Research Reports, 2014)
An experiment was conducted to determine the impact of increasing levels of Algamune ZPC (Algal Scientific Corporation, Plymouth, MI) on growth performance and porcine circovirus type 2 (PCV2)-specific immune response of nursery pigs housed under commercial conditions. Algamune ZPC is a polysaccharide-zinc complex feed additive composed of 35% Î²-1,3-glucan extracted from algae and 10% zinc. A total of 2,484 pigs (PIC 337 × 1050, initially 15.7 lb) were used in a 40-d trial. After feeding a common pelleted diet for 7 d after weaning, pigs were allotted to 1 of 6 dietary treatments in a randomized complete block design with 14 or 16 replicate pens and 27 pigs per pen. All pigs were vaccinated with PCV2 and M. hyopneumoniae vaccines (1 mL Fostera PCV and 1 mL Respisure- One; Zoetis, Florham Park, NJ) at d 3 after birth and at weaning. Blood samples of 72 pigs (12 pens per treatment) were collected on d 2, 18, and 38. The 6 experimental diets were fed in two phases (d 0 to 12 and 12 to 40). Dietary treatments included: a negative control diet fed in both phases (1,910 and 110 ppm of zinc oxide in Phase 1 and 2, respectively); the negative control diet with 104, 208, 423, and 625 ppm added Algamune ZPC for both Phase 1 and Phase 2; and a negative control diet with 423 ppm added Algamune ZPC fed during phase Phase 1 followed by the negative control in Phase 2. From d 0 to 40, increasing Algamune ZPC tended to decrease then increase (quadratic, P = 0.09) ADG and increase (linear, P = 0.10) ADFI. No differences were observed in F/G. There were no differences (P>0.54) in ADG, ADFI or F/G in pigs fed 423 ppm Algamune ZPC in both phases compared with pigs fed 423 ppm Algamune ZPC only in Phase 1 and the negative control diet fed in Phase 2. The lowest removal rates were observed among pigs assigned to 423 ppm Algamune ZPC only in Phase 1 or in both phases (0 and 0.27%, respectively). No evidence of differences was detected in PCV2-neutralizing antibody titers on d 16, but the titers decreased on d 38 (linear, P = 0.04) with increasing Algamune ZPC. In conclusion, including up to 625 ppm of Algamune ZPC in nursery pig diets from 16 to 56 lb had minimal impact on growth performance. Also, modulation of the specific immune response to PCV2 on d 38 after weaning was negatively related to increasing Algamune ZPC under commercial conditions. Key words: Î²-glucans, immune response, nursery 1 The authors thank Algal Scientific Corporation, Plymouth, MI, for providing Algamune ZPC and for partial financial support. 2 Appreciation is expressed to New Horizon Farms for use of pigs and facilities and to Lanny Bosma, Shannon Paulson, and Marty Heintz for technical assistance. 3 Department of Diagnostic Medicine/Pathobiology, College of Veterinary Medicine, Kansas State University. 64 SWINE DAY 2014 Introduction Feed additives that could modulate the immune response of nursery pigs may serve as an alternative to growth-promoting antimicrobials. Î²-glucans are polysaccharides containing only glucose and are found as cellulose in plants; cell walls of yeast, fungi, or bacteria; and bran of cereal grains. Research has shown that dietary inclusion of 0.025% of yeast-derived Î²-glucans in nursery pig diets increased ADG, ADFI, and pig BW on d 28 after weaning (Dritz et al., 19954). In addition, pigs fed 0.025% Î²-glucans had an increased mortality rate compared with pigs fed the negative control or 0.05% Î²-glucans, but Li et al. (20065) observed an improvement in the immune system of pigs fed yeast-derived Î²-glucans. Most research has been performed with Î²-glucans extracted from specific yeast cell wall components. A new product, Algamune ZPC (Algal Scientific Corporation, Plymouth, MI), contains Î²-glucans extracted from algae and is a polysaccharide-zinc complex (35% Î²-1,3-glucan and 10% zinc). Therefore, the objective of this experiment was to determine the impact of Algamune ZPC on growth performance, removal rate, and PCV2-specific immune response of nursery pigs housed under commercial conditions. Procedures The protocol for this experiment was approved by the Kansas State University Institutional Animal Care and Use Committee. The study was conducted at a commercial research nursery in southwestern Minnesota. The facility was totally enclosed, environmentally controlled, and mechanically ventilated. Pens were distributed across 2 rooms and had completely slatted flooring and deep pits for manure storage. Each pen was equipped with a 5-hole stainless steel dry self-feeder and a pan waterer for ad libitum access to feed and water. Daily feed additions to each pen were accomplished through a robotic feeding system (FeedPro; Feedlogic Corp., Willmar, MN) capable of providing and measuring feed amounts for individual pens. A total of 2,484 pigs (PIC 337 × 1050, initially 15.7 lb BW) were used in a 40-d trial. Pigs were weaned at 19 d of age and were initially fed a common pelleted diet for 7 d before the start of the experiment. On d 7 after weaning, pigs were weighed and pens of pigs were allotted to 1 of 6 dietary treatments in a randomized complete block design. Each treatment had 14 or 16 replicate pens and 27 pigs per pen, with each pen containing a mix of barrows and gilts. All pigs were vaccinated with porcine circovirus type 2 (PCV2) and M. hyopneumoniae vaccines (1 mL Fostera PCV and 1 mL Respisure-One; Zoetis, Florham Park, NJ) on d 3 after birth and at weaning. Blood samples of 72 pigs (12 pens per treatment, 1 pig per pen) were collected on d 2, 18, and 38 of the trial and were submitted to the Kansas State Veterinary Diagnostic Laboratory to measure PCV2 antibody titers using indirect immunofluorescence (IFA) assay.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Î²-glucans; Immune response; Nursery pig